How Does Neo-liberalism Explain the Likelihood of China’s Threat Towards United States’ Hegemony in the 21stCentury - Gabiella, Dennyza (JAS (Journal of ASEAN Studies), 2016)
By means of neo-liberal perspective and supported by empirical evidences, this essay argues that despite the neo-realists’ assumption of China’s potential threat over the current liberal international system (which is led by the United States as the hegemonic state), China’s tremendous economic rise can be accommodated peacefully for two reasons. The first reason is that China’s economic rise itself is enabled by the existing liberal international system, which perpetuated by the United States’ and its allies. Whereas the second reason is because it is less costly for the one-party-rule China to achieve its national interests by maintaining a cooperative strategic relationship with the United States compared to challenging the United States’ leadership and revising the current liberal international system. This essay will be organized into three main parts. The first part of this essay will elaborate the theoretical debate between neo-realism and neo-liberalism perspectives and their assumptions about the ‘China Threat Theory’. The second part will provide empirical evidences to support the analysis of China’s likelihood to challenge United States’ hegemony in the 21st century based on the neo-liberalism perspective. The third part will analyse the potential of China to become the regional hegemonic power in South East Asia, and then followed by a conclusion.